2010
DOI: 10.1152/ajpheart.00369.2010
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of ER-α-dependent NO production in resveratrol-mediated inhibition of restenosis

Abstract: veratrol (Resv), a red wine polyphenol, is known to exhibit vascular protective effects and reduce vascular smooth muscle cell mitogenesis. Vascular smooth muscle cell proliferation is a critical factor in the pathogenesis of restenosis, the renarrowing of vessels that often occurs after angioplasty and/or stent implantation. Although Resv has been shown to be an estrogen receptor (ER) modulator, the role of the ER in Resv-mediated protection against restenosis has not yet been elucidated in vivo. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
0
18
3
Order By: Relevance
“…[2][3][4] Epidemiological studies have also shown that red wine consumption was irreversibly correlated to a risk of coronary heart disease. 5) In practice, resveratrol inhibits the oxidation of human low-density lipoproteins, 6,7) platelet aggregation, 8) and the proliferation of vascular smooth muscle cells (VSMCs) [9][10][11][12][13][14] which can prevent the pathogenesis of atherosclerosis. Resveratrol is therefore believed to be a strong candidate for explaining the ''French paradox'' that indicates the reduction in coronary heart disease observed with red wine drinkers.…”
mentioning
confidence: 99%
“…[2][3][4] Epidemiological studies have also shown that red wine consumption was irreversibly correlated to a risk of coronary heart disease. 5) In practice, resveratrol inhibits the oxidation of human low-density lipoproteins, 6,7) platelet aggregation, 8) and the proliferation of vascular smooth muscle cells (VSMCs) [9][10][11][12][13][14] which can prevent the pathogenesis of atherosclerosis. Resveratrol is therefore believed to be a strong candidate for explaining the ''French paradox'' that indicates the reduction in coronary heart disease observed with red wine drinkers.…”
mentioning
confidence: 99%
“…In earlier studies, RSV treatment was shown to attenuate restenosis [140][141][142] with reduced neointimal hyperplasia [140][141][142][143][144] in artery injury models of rabbits [140], rats [141,143,144] and mice [142]. In addition, RSV upregulated the expression of eNOS [141][142][143], p-eNOS [143], NO [142], Sirt1 [143], p-AMPK [143] while it downregulated that of iNOS [143], platelet endothelial cell adhesion molecule (PECAM) [143], MMP-9 [143], 8-iso-PGF2α [144], MCP-1 [144], and IL-6 [144]. More recently, it has been found RSV treatment prevented restenosis with a reduction of neointimal hyperplasia in carotid artery-injured [142][143][144] and femoral wire-injured [143] models with rodents.…”
Section: Restenosismentioning
confidence: 99%
“…In addition, RSV upregulated the expression of eNOS [141][142][143], p-eNOS [143], NO [142], Sirt1 [143], p-AMPK [143] while it downregulated that of iNOS [143], platelet endothelial cell adhesion molecule (PECAM) [143], MMP-9 [143], 8-iso-PGF2α [144], MCP-1 [144], and IL-6 [144]. More recently, it has been found RSV treatment prevented restenosis with a reduction of neointimal hyperplasia in carotid artery-injured [142][143][144] and femoral wire-injured [143] models with rodents. The suppressive activity of RSV on neointimal hyperplasia was abolished in ER-α -/-mice [142], endothelial NOS (eNOS) knockout mice [143], and in N G -nitro-L-arginine methyl ester (L-NAME)-co-treated mice [142] or rats [143], suggesting that RSV exerts the effect through ER-α-dependent NO production [142].…”
Section: Restenosismentioning
confidence: 99%
See 2 more Smart Citations